(untitled) (Iraqi Journal of Medical Sciences, 2018)
Background: Sodium valproate has turn out to be the most commonly prescribed antiepileptic drug (AED) worldwide. It is also prescribed to diabetic mellitus (DM) patient for treatment of neuropathic pain. Changes in lipid levels and lipid metabolism usually accompanied with diabetic disease leading to increases in circulating levels of free fatty acids (FFA), triglycerides and dense low-density lipoprotein together with reduced levels of high-density lipoprotein cholesterol levels. Objective: To investigate the effect of sodium valproate on lipid profile and glucose level and highlight these effects with and without diabetic disease. Methods: Thirty-two healthy, local domestic rabbits of both sexes were used in the present study. Animals were allocated into two main groups, group A and B. According to induction of diabetes both groups received the same food and put in the same environmental condition. blood glucose level and lipid profile has been done for all groups. Results: There was significant difference in the blood glucose level in the normoglycemic rabbits treated with sodium valproate (200 mg/kg) compared to the untreated (negative control group). The effect of valproate was also observed by the significant difference of blood glucose level in alloxan-induced diabetic rabbits treated with sodium valproate (200 mg) compared with the positive control group. Also, we have statistically observed the significant increase in total cholesterol (TC), low density lipoprotein – cholesterol (LDL-C), and triglyceride (TG) levels in normoglycemic rabbits treated with sodium valproate (200 mg/kg) compare to the negative control group, however, there is no significant difference regarding the high-density lipoprotein – cholesterol (HDL-C) level. As for the alloxan-induced diabetic rabbits, there was a statistically significant difference observed indicated an increase in level of TC, LDL-C, and TG and a decrease in HDL-C. Conclusion: The effect of sodium valproate on glucose level and lipid profile in diabetic rabbits could reflect a possible hypoglycemic and dyslipidemic effects which could be dangerous if the patient is on anti- diabetic drugs with or without cardiovascular accident, although it may be dose-dependent and still falls in the hypothesis field but further experimental studies on human are needed to explore this theory. Keywords: Sodium valproate, anticonvulsants, glucose, lipid Citation: Abdul Bari MA. Sodium valproate effects on lipid profile and glucose level in normal and diabetic rabbits. Iraqi JMS. 2018; 16(3): 247-257. doi: 10.22578/IJMS.16.3.4